Cortical excitability and brain function in patients with insomnia: a pilot transcranial magnetic stimulation and functional near-infrared spectroscopy study - Luo, Jiali; Chen, Qi (Frontiers in Neuroscience, 2026)
BackgroundInsomnia significantly impairs well-being, cognitive function, and social functioning, yet subjective psychological assessments often yield equivocal results regarding the extent of this impairment. Neural function may underlie this discrepancy and offer a more precise foundation for guiding treatment. This study therefore employed non-invasive transcranial magnetic stimulation (TMS) and functional near-infrared spectroscopy (fNIRS) to investigate cortical excitability and brain activity patterns in patients with short-term insomnia disorder (SID) and chronic insomnia disorder (CID), aiming to identify associated neural function changes.MethodsWe recruited 30 patients with SID and 30 with CID. For all participants, cortical excitability was assessed by measuring the resting motor threshold (RMT) via single-pulse TMS. fNIRS was utilized to measure the concentrations of oxy-hemoglobin (Oxy-Hb) and functional connectivity in the cerebral cortex during a verbal fluency task (VFT).ResultsOur study revealed that patients with SID had significantly lower RMT and higher cortical activation in the hemodynamic responses of Oxy-Hb in the bilateral dorsolateral prefrontal cortex (DLPFC), the left medial prefrontal cortex (mPFC), and the right temporal lobe (TL) than CID patients during the 60 s task period. The CID group showed significantly lower average inter-channel connectivity strength compared to the SID group. Moreover, the CID group exhibited significantly lower connectivity from the right DLPFC to the left DLPFC and the left mPFC compared to the SID group. For the SID patient group, we found that the RMT was negatively correlated with mean Oxy-Hb changes in the left mPFC. Conversely, functional connectivity between the left DLPFC and TL showed a positive correlation with RMT. Furthermore, diminished connectivity between the left TL and mPFC was associated with elevated cortical excitability.ConclusionPatients with CID demonstrated lower cortical excitability, decreased brain activity, and reduced task-related functional connectivity relative to the SID group. This finding indicates distinct neurological profiles between short-term and chronic insomnia, a distinction that will be critical for tailoring effective neuromodulatory interventions.